Preoperative antibiotic prophylaxis practice and guideline adherence in Jordan: a multi-centre study in Jordanian hospitals - Sayer I Al-Azzam; Karem H Alzoubi; Nizar M Mhaidat; Rania D Haddadin; Majed M Masadeh; Haitham N Tumah; Arabieh Magableh; Noor K Maraqa (Journal of Infection in Developing Countries)
Introduction: The use of antimicrobial prophylaxis for surgical procedures is one of the measures employed to prevent the development of surgical site infections (SSI). The appropriate choice of antimicrobial agents, dosage regimen, timing, duration and use of intravenous route must be evidence based. This study aimed to assess the practice of surgical antibiotic prophylaxis and adherence of practitioners to the American Society of Health-System Pharmacists (ASHP) guidelines for antimicrobial prophylaxis in surgery and to explore reasons for non-compliance. Methodology: A cross-sectional study was conducted in 20 Jordanian hospitals from October 2006 to June 2007. A questionnaire was designed to collect information from physicians regarding the practice of surgical antibiotic prophylaxis (SAP), references used for guiding SAP practice, prevalence of surgical site infection (SSI), and causative microorganisms. Results: SAP was employed in almost all surgical departments of hospitals. The improper timing of antimicrobial administration for SAP was attributed to lack of knowledge of the guidelines (46.1%), while the improper antimicrobial choice was ascribed to drug unavailability (61.8%). Conclusion: This study shows that physicians are aware of the importance of antimicrobial prophylaxis before surgical procedures. However, further efforts are needed to ensure the implementation of the standard SAP guidelines in Jordanian hospitals.